Preparation and Thermal and Anti-UV Properties of Chitosan/Mica Copolymer. (23rd December 2010) - Huang, Yih-Sheng; Yu, Sheng-Haur; Sheu, Yea-Ru; Huang, Kuo-Shien
Abstract : This experiment aims to produce a free radical while annoying the oxidizing-reducing reagent of the ammonium persulfate and the sodium bisulfite under nitrogen, then trigger copolymerization between modified-mica and chitosan to prepare a variety of copolymers. This experiment also aims to study the related properties of these copolymer materials. The experimental data shows that the copolymer has more thermal stability and better absorption of UV than chitosan. But the above physical properties will be less if the mica ratio in copolymer is more than 8%. On the other hand, the SEM photo of the microstructure also shows that the modified mica distributes homogeneously on the surface of the film of the copolymer.